Problematika Kesulitan Membaca pada Anak Kelas Rendah: Peran Guru dalam Mengatasi Kesulitan Membaca - Nur`aini, Prasistya Cahya; Waheda, Isti; Nurhalisa, Meinda (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Reading is a major focus in lower education, especially at primary school level. This study discusses the factors of initial reading difficulties faced by students as well as the role of teachers in solving reading challenges. Research shows that groups of students with reading difficulties tend to have lower learning outcomes. Internal and external factors such as students' physical condition, family environment and school environment are factors that hinder reading. The teacher's contribution in solving reading problems is very crucial. Teachers are not only instructors, but also mentors or guides, motivators, and facilitators. The research method uses literature study, where the data collection system in this research is obtained from literature analysis through book and journal references that are relevant to the problems identified. Relevant research results include the role of teachers in overcoming reading difficulties, such as being a demonstrator, class manager, facilitator, and evaluator. Factors causing reading difficulties include the student's physical condition, lack of family attention, and an unsupportive school environment